SHOULD ENGLISH-ONLY METHOD BE APPLIED IN EFL CLASSES - MARIA PUSPA SARI (Sriwijaya University Learning and Education International Conference, 2016)
The challenge that many English learners in Indonesia cannot speak English fluently has been an issue for years. Numerous studies have been conducted to answer the question and they blamed the methods applied by English teachers. Also, researchers have proposed many methods to boost English learners‟ communicative skill especially speaking skill. However, most methods used in English classes do not become habits as teachers may change them to avoid boredom in the class. Being able to speak English is about how to make speaking English as habit, so students will automatically switch their language as they enter their English classes. Some teachers across the globe force students to speak English and make it as a habit in their classes. The English-only method is believed as an effective way to build learners‟ confidence and fluency in speaking. How is this method applied in an EFL classroom? How does it affect learners‟ confidence and fluency in speaking? This paper aims to provide alternative way with its controversy to increase English learners‟ speaking ability.